A new deep water chiton (Mollusca: Polyplacophora) from hydrothermal vent ecosystems in the Okinawa Trough, Japan - Sigwart, Julia D.; Chen, Chong (Zootaxa, 2018)
Recent expeditions exploring deep-sea hydrothermal vent ecosystems in the Okinawa Trough, East China Sea resulted in the collection of a hitherto undescribed species of polyplacophoran mollusc found living at three different vent fields at depths of 950–1178 m. This new chiton is a member of the small lepidopleuran family Protochitonidae and is morphologically similar to Hanleyella japonica Saito, 1997. The two species differ in small morphological differences of the valve shape and elevation, are divergent in the standard molecular barcoding mitochondrial gene cytochrome oxidase I (COI), and furthermore the known distribution range of H. japonica is considerably more northern and also shallower. The new species is described herein as Hanleyella henrici n. sp. Additional in situ observations taken in the course of collecting material for this study indicates that chitons are more abundant in the vicinity of hydrothermal vents than was previously appreciated, and perhaps more speciose.